Dietary intake and supplement use of under 21 rugby players, Blue Bulls - Smith, Veronica Christine (University of the Free State, 2007)
The need for accurate sports nutrition information is increasing. Whether the athlete’s performance is recreational or elite it will be influenced by what he eats or drinks. More than half of the athletic populations are supplement users, although the prevalence ranges between sports. Despite the lack of evidence from the benefit from the use of most nutritional supplements, commercial promotion of their use is a thriving and highly influential business. Little research has been done on the dietary intake and supplement use of South African and international rugby players. The purpose of this study was to determine the dietary intake and the use of supplements by u/21 male rugby players with the view to develop suitable nutrition education messages according to the problems related to dietary and supplement use; and to set up practical guidelines for the safe and effective use of supplements. Common to rugby, is the intermittent, high intensity of play, which places great demands on both anaerobic and aerobic energy systems. Physical activity, exercise performance and recovery from exercise are enhanced by optimal nutrition. A fundamental role of nutrition in sport is to supply fuel for energy as well as all the essential macro - and micronutrients and fluid. Exercising individuals universally want to perform better and are willing to try almost anything that offers a promise of better performance. Consumption of dietary supplements and ergogenic aids have become commonplace among athletes. The main aim was to determine the dietary intake and the use of supplements by 30 u/21 male rugby players from the Blue Bulls. A pilot study was conducted on 5 of the u/20 rugby players from the UP prior to the main study. A background information questionnaire, supplement questionnaire and four-day food record were used to collect data. Of the 30 players, 26 players returned the background information questionnaire and the supplement questionnaires. Two incomplete questionnaires could not be used. The required information could thus be collected only from 24 players. The average dietary intake of the rugby players without supplements, were adequate, except for the total CHO, dietary fibre, vitamin E, calcium, magnesium and iodine intakes that were inadequate. The average fluid intake was also lower than the proposed maximum intake. The majority of the study population used cordials and carbonated beverages for rehydration purposes. The alcohol intake of the study population was low except for on the competition day. Supplementation did not contribute significantly to the dietary intakes of the rugby players, except for an adequate vitamin E intake. The rugby players ingested an average high fat, SFA, cholesterol, sodium and chloride intakes. The energy and CHO intakes compared to the SSR were inadequate on the training day and both exercise days, respectively. The majority of the study population used supplements. Protein powders were most often used. Most of the supplements were used in amounts that were within the recommendations. Supplements were used before and after exercise, in no specific pattern. Muscle building and repair was the reason most used for supplement use. Before any supplementation practices is considered by the rugby players, an adequate diet should be followed. Rugby players need more education and practical guidelines on their dietary habits; the benefit of a high carbohydrate, low fat diet on health and sports performance; the importance of rehydration strategies, fluid intake and types of fluid ingested; the safe and effective use of supplements.

Die behoefte aan akkurate sportvoeding neem al meer toe. ‘Meer as helfte van die atletiese populasie is supplementverbruikers, alhoewel die voorkoms daarvan wissel tussen sporte. Die kommersiële verspreiding van supplemente is ‘n invloedryke besigheid, ten spyte van die tekort aan voldoende bewyse. Navorsing oor die dieetinname en supplement gebruik van Suid Afrikaanse en internasionale rugby spelers is min. Hierdie studie is gedoen om die dieetinname en supplement gebruik van die o/21 rugby spelers te bepaal. Die doel was om voedingsboodskappe volgens geidentifiseerde probleme saam te stel; en om praktiese riglyne vir die veilige en effektiewe gebruik van supplemente, daar te stel. Rugby is ‘n hoë intensiteit spel wat groot fisieke vereistes op die anaerobiese en aerobiese energie sisteme plaas. Optimale voeding bevorder fisieke aktiwiteit, sport prestasie en herstel na oefening. Die verskaffing van energie asook essensiële makro – en mikrovoedingstowwe en vloeistof is die belangrikste rol van voeding in sport. Alle sportlui wil graag beter vaar en sal enige iets probeer om sport prestasie te verbeter. Die gebruik van dieetsupplemente en ergogene hulpmiddels kom algemeen voor onder sportlui. Die hoofdoel van die studie was om die dieetinname en supplementgebruik van 30 o/21 rugbyspelers van die Blou Bulle te bepaal. ‘n Loodstudie is op 5 o/21 rugbyspelers van die UP gedoen voor die aanvang van die studie. ‘n Agtergrondinligting vraelys, supplement vraelys en 4-dag voedselrekord is gebruik om inligting te versamel. Slegs 26 van die 30 rugby spelers het die agtergrondinliging vraelys en supplement vraelys ingehandig. Twee onvoltooide vraelyste kon nie gebruik word nie. Gevolglik kon die nodige inligting slegs van 24 spelers verkry word. Die gemiddelde mediaan dieetinname van die rugby spelers met en sonder supplementgebruik, was volgens die RDA/AI en aanbevelings vir gesonde individue toereikend, behalwe die totale koolhidraat, dieetvesel, vitamien E, kalsium en magnesium innames wat ontoereikend was. Die gemiddelde mediaan van vloeistofinname was laer as die aanbevole maksimum inname. Die meerderheid van die studiepopulasie het aanmaakkoeldrank en gaskoeldranke as rehidrasie drankies gebruik. Die alkoholinname van die studiepopulasie was laag, behalwe vir die hoër inname op die kompetisie dag. Supplementasie het nie tot die dieetinname van die rugbyspelers bygedra nie, behalwe vir die toename in vitamin E inname met supplementgebruik. Die gemiddelde mediaan van suiker, vet, versadigde vette, cholesterol, kobalamin, natrium en chloried inname was hoër as die RDA/AI en aanbevelings vir gesonde individue. Die mediaan vir energie en koolhidraat innames was volgens die sport spesifieke aanbevelings ontoereikend op die oefendag en kompetitisiedag. Die meerderheid van die studiepopulasie het supplemente gebruik. Proteinpoeiers is die meeste gebruik. Die meeste supplemente is gebruik in hoeveelhede wat binne die aanbevelings vir supplementgebruik is. Supplemente is gebruik voor en na oefening, volgens geen spesifieke patroon. Spierbou en herstel is as redes vir supplementgebruik verskaf. Rugbyspelers moet eerstens ‘n toereikende dieet volg, voordat supplementasie oorweeg kan word. Rugby spelers benodig meer voedingonderrig en praktiese riglyne oor dieetgewoontes; die voordele van ‘n hoë koolhidraat, lae vet dieet vir gesondheid en sportprestasie.; die belang van rehidrasie, vloeistofinname en tipes rehidrasie drankies wat ingeneem word; asook die effektiewe en veilige inname van supplemente.
Dissertation (M.Sc. (Nutrition and Dietetics))--University of the Free State, 2007
Keywords: Dietary intake; Supplements; Sports nutrition; Rugby player; Macronutrients; Micronutrients; Fluid; Nutritional ergogenic aids; Exercise; Performance; Physical fitness; Football players -- Nutrition; Dietary supplements -- Evaluation; Sports -- Nutritional aspects